A Statistical Assessment of Drinking Water Quality: A Case Study of Doburca Treatment Plant, Bursa - Yılmaz, Damla; Aras, Egemen; Vaheddoost, Babak (My University, 2024)
In order to provide and maintain urban health standards, assessing the quality of drinking water is an essential step. As a result of different pollutant factors (climate, heavy metals, vegetation, human activities, etc.), it is inevitable that the quality of water resources decreases day by day. In this study, the data of 21 water samples taken between January 2021 and June 2021 from the water drinking facility providing drinking water to Bursa were examined. Firstly, the strength and direction of the relationship between 10 different parameters (electrical conductivity (EC), copper (Cu), nickel (Ni), nitrate (?NO?_3^-), arsenic (As), iron (Fe), total dissolved substances (TDS), total alkalinity (TA), total hardness (TH) and dissolved oxygen (DO)) were evaluated with the help of relation analysis, water quality index, and polynomial curve fitting. The relationship of the parameters that do not have a linear correlation was also interpreted and finally, as a result of using the weighted arithmetic water quality index (WAWQI), it was determined that the potability of the water quality in the allocated water reservoir was at the 'excellent' level and fulfills the requirements.
Keywords: Surface water; Correlation analysis; Water quality index; Treatment plants